Kajian Pustaka Sistematis tentang Perencanaan Kegiatan Pembelajaran : Pemilihan Materi Pembelajaran - Nur Satriani; Muhammad Hud Ashaq; Bahri Bahri (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Determining the learning technique for picking the subject matter is the purpose of this essay. This paper employs a descriptive qualitative research methodology. This study use the literature review methodology for data collecting. The paper concludes with a discussion on learning planning, emphasizing the selection of learning resources categorized into four types: facts, concepts, principles, and procedures. The criteria for selecting topic matter for development in the learning system comprise seven elements: (1) criteria for learning objectives; (2) elaborated subject matter; (3) relevance to student needs; (4) alignment with societal conditions; (5) inclusion of ethical aspects in the subject matter; (6) systematic and logical organization of lesson material; (7) sourcing of lesson material from standard textbooks, expert educators, and the community. A teacher must prepare four elements while designing a subject: subject materials, competency or learning objectives, learning strategies or procedures, and learning evaluation. The criteria for selecting educational resources encompass relevance, consistency, and adequacy. This indicates that learning must be pertinent to attaining competency criteria and fundamental competencies.